Subsurface warming associated with Pacific Summer Water transport toward the Chukchi Borderland in the Arctic Ocean - Miaki Muramatsu; Eiji Watanabe; Motoyo Itoh; Jonaotaro Onodera; Kohei Mizobata; Hiromichi Ueno (Scientific Reports)
Abstract Recent rapid sea ice reduction in the Pacific sector of the Arctic Ocean is potentially associated with inflow of Pacific-origin water via the Bering Strait. For the first time, we detected remarkable subsurface warming around the Chukchi Borderland in the Arctic Ocean over the recent two decades (i.e., the early 21st century). A statistically significant decadal trend of 16.6 ± 10.6 MJ m− 2 year− 1 in the subsurface ocean heat content during 1999–2020 was captured by shipboard hydrographic data, and associated with the transport of Pacific Summer Water from Barrow Canyon northwest of the Alaskan coast, where similar warming appeared. Satellite-derived geostrophic ocean velocity indicated that the northwestward ocean current flowing from Barrow Canyon to the Chukchi Borderland became faster in the late 2010s, in association with southeastward shift of the Beaufort Gyre, circulating clockwise around the Canada Basin. Therefore, we suggest that warming of the Pacific Summer Water passing over the Chukchi shelf and intensification of the northwestward ocean current along the shelf–basin boundary both acted to enhance the heat transport and contributed to the positive trend in downstream subsurface ocean heat content. Our findings fill important gaps in the understanding of ocean heat distribution/transport, which is a key factor for sea ice freezing/melting, in the central Arctic.